Technical and Economic Assessment of Choosing Location of Step-Down Transformer Substation - V. V. Krotenok; Yu. V. Rabskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a problem concerning existing methods for  choosing location of a step-down transformer substation (STS). Algorithms and program segments for calculation of STS location using  existing and CG methods have been developed in the paper. The paper presents results of investigations numerically and graphically and it also contains an assessment of the CG method efficiency.